Comparison of Functional Shoulder Recovery after Conservative versus Surgical Treatment in Patients with Grade III Acromio-Clavicular Dislocation (Journal of Fatima Jinnah Medical University, 2018)
Objective: To compare the functional shoulder recovery after conservative versus surgical treatment in patients with grade III acromio-clavicular dislocation. Design: It was a randomized controlled trial. Place and Duration of Study: This study was conducted at the Department of Orthopedic Surgery, Sir Ganga Ram Hospital, Lahore over 2 years period from June 2013 through June 2015. Patients and Methods: 80 patients of both genders aged between 18-65 years presenting with Rockwood Grade-III AC Dislocation were enrolled. These patients were then divided into following two groups randomly using lottery method. Patients in Group-A underwent Conservative Treatment which involved resting of the arm in a broad arm sling for 3 weeks followed by physiotherapy. While patients in Group-B underwent Surgical Treatment which involved open reduction and stabilization of the joint using a hook plate followed by physiotherapy starting at 2 weeks post-operatively. Outcome was was described by using constant score (Appendix-I) in terms of mean±sd after 6 weeks of treatment. Results: The age of the patients ranged from 18 years to 65 years with a mean of 41.63±11.41 years. 37 (46.3%) of the study participants were male while 43 (53.8%) were female. In 45 (56.3%) patients right side was involved while in 35 (43.8%) patients left side was involved. However, there was no significant difference between the two groups in terms of mean age (p=0.267), gender (p=0.501) and side involved (p=0.499). When compared the outcome, surgical treatment was better than conservative treatment in terms of mean improvement in pain score (11.68±3.10 vs. 9.48±3.13; p=0.0002), mean activities of daily living score (16.80±3.15 vs. 12.45±4.10; p=.000), mean movement score (34.98±4.22 vs. 26.53±7.01; p=0.000) and mean strength score (21.80±2.61 vs. 17.95±4.05; p=0.000). The overall mean constant score was significantly better in Group-B than Group-A (85.25±6.029 vs. 66.40±9.58; p=0.000). There was no statistically significant difference when compared the mean constant score among age groups (p=0.824), gender (p=0.727) and side involved (p=0.802) confirming that surgical treatment was better than conservative treatment in all age groups and gender and was not affected by side involved. Conclusion: Surgical treatment is better than conservative treatment in terms of significantly higher mean of constant score in patients with Rockwood Type-III AC dislocation.
Keywords: Rockwood Type-III AC dislocation, Conservative Treatment, Surgical Treatment, Mean of Constant Score